The Empirical Dimensionality of the Job Characteristic Inventory - Griffin, Ricky W.; Moorhead, Gregory; Johnson, Bruce H.; Chonko, Lawrence B. (Academy of Management Journal, 1980)
The article discusses a study designed to asses the cross-sample stability of the job characteristics inventory (JCI). According to the author, the JCI could have utility for task design research. Also discussed is the Job Diagnostic Survey (JDS) as applied to employees in organizations. The author notes that future research should be conducted to determine the psychometric properties of the JCI. The data from the study indicates that the dimensionality of tasks measured by the JCI could be less sample-specific than when measured by the JDS.